Growth and Instability of Inland Fish Production in India - Sharma, Hemant Sharma (Fishery Technology, 2017)
The growth value of inland fish production during1995-2014 was significant in almost all states in thecountry. During 2005-14, the annual growth rate ininland fish production was highest and significantin states of Jharkhand (17.30%) and Andaman &Nicobar Islands (16.50%). The higher instability ofinland fish production in the states of Andaman &Nicobar Islands, Goa, Dehli and Mizoram did notdeter from attaining high growth rates. Temporalchanges in inland fish production declined in sixstates viz., Arunachal Pradesh, Delhi, Goa Gujarat,and Madhya Pradesh during the 2005-14 comparedto previous period. However, high up and down inthe inland fish production during 2005-14 wasnoticed in all the states. High growth and highinstability in the production of inland fish duringthe current decade needs special attention of thepolicy makers and researchers.